Study on the Spawning Techniques of Jelawat Fish (Leptobarbus hoevenii) at Balai Perikanan Budidaya Air Tawar (BPBAT) Sungai Gelam - Anggraini, Gira; Arbajayanti, Rahma Dini; Rolin, Febrina; Pangentasari, Dwinda; Leni, Yusyam; Hafidz Ibnu Khaldun, Muhammad; Putinur, Putinur; Roiska, Riris; Bareta, Ainun Rohmawati; Hasanah, Hasanah (Mantis Journal of Fisheries, 2025)
This study aims to determine the spawning techniques of Leptobarbus hoevenii fish at the Sungai Gelam Freshwater Aquaculture Center (BPBAT). Activities include maintaining prospective broodstock, selecting mature broodstock, injecting ovulation hormones, and the spawning process, stripping, egg handling, water quality monitoring to highlight its importance, and embryo development. Ovaprim hormone injections were administered to the female broodstock four times and once to the male broodstock to stimulate ovulation. The stripping process was carried out after ovulation and was followed by dry mixing of eggs and sperm before being spread into the hatching tank. The results showed a fertilization rate of 63,08% and a hatching rate of 9,73%, which were influenced by gamete quality and the physiological condition of the broodstock. Observations of embryogenesis showed developmental stages ranging from morula, blastula, gastrula, to organogenesis before the eggs hatch into larvae. Water quality parameters during the study were in the optimal range for spawning, namely pH 7,24–7,77, temperature 27–30,5°C, and DO 3,53–5,58 mg/L. The results of this study explain that the success of Hoven’s carp fish seeding is highly dependent on the readiness of the broodstock, the application of artificial spawning techniques, and good water quality management.